“When a dog bites someone”: Community and service provider dynamics influencing access to integrated bite case management in Chad - Madjadinan, Alladoumngar; Mbaipago, Nodjimbadem; Sougou, Ndèye Marème; Diongue, Mayassine; Zinsstag, Jakob; Heitz-Tokpa, Kathrin; Lechenne, Monique (Frontiers in Veterinary Science, 2022)
This study aims to identify factors on the community, the human health and the animal health provider level that determine access to Post Exposure Prophylaxis (PEP) and animal rabies diagnosis in the light of a future integrated bite case management (IBCM) approach for rabies control in Chad. The study was embedded in an overall project conducted from 2016 to 2018, to determine rabies burden and vaccine demand in West and Central Africa. Data collection took place during the projects closing workshops with stakeholders organized between August and September 2018 in the three study zones in Chad covering Logone Occidental and Ouaddaï province and parts of Hadjer Lamis and Chari Baguirmi province. A qualitative approach based on focus group discussion and in-depth interviews was used to get insights on access to care and animal investigation after suspected rabies exposure. A total of 96 participants, including 39 from the community (bite victims, dog owners) and 57 human and animal health providers (health center managers, chief veterinary officers, chief district medical officers, chiefs of livestock sectors) contributed to the study. Based on an existing conceptual framework of access to health care, several points of dissatisfaction were identified, in particular the unaffordability of human rabies vaccine for PEP (affordability) and the distance to travel to a health facility in case of a bite (accessibility). In addition, there are unfavorable attitudes observed highlighted by the importance given to traditional or local rabies care practices to the detriment of PEP (acceptability) and a low level of knowledge among Chadian communities regarding bite prevention, coupled with a very inadequate information and awareness system regarding the disease (adequacy). As for human and veterinary health services, both sectors suffer from insufficient resources for PEP on the human health and rabies diagnosis on the veterinary side impacting negatively on availability and accessibility of both these services. Action to improving provision of rabies health services and increasing knowledge about risk and prevention of the disease among the population need to be undertaken to implement IBCM, improve access to PEP and achieve the goal of eliminating dog mediated human rabies by 2030 in Chad.